Solid State Lasers XI 2002
DOI: 10.1117/12.459001
|View full text |Cite
|
Sign up to set email alerts
|

Compact active mirror laser (CAMIL)

Abstract: This work presents concept and scaling considerations for a solid-state laser with a gain medium disk operating in the active mirror mode. The disk is of composite construction formed by bonding undoped optical medium to the peripheral edges of a gain medium disk. Pump diode anays are placed around the perimeter of the composite disk and pump light is injected into the undoped edge. With proper choice of lasant doping, diode placement and diode divergence, a uniform laser gain can be achieved across large port… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
4
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 20 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…The resulting SSHEL is sufficiently lightweight and compact for integration onto a medium-size land vehicle, Figure 9. Additional improvements are expected with the use of side-pumped CAMIL [7].…”
Section: Hardware Integrationmentioning
confidence: 94%
See 1 more Smart Citation
“…The resulting SSHEL is sufficiently lightweight and compact for integration onto a medium-size land vehicle, Figure 9. Additional improvements are expected with the use of side-pumped CAMIL [7].…”
Section: Hardware Integrationmentioning
confidence: 94%
“…In either case, the substrate acts as a 'backbone' that mitigates thermal deformations of the disk. Pump radiation is injected into the disk either through one of the large faces (face pumping, Figure 4a) [6] or through the peripheral edge (side pumping) [7]. Face-pumped CAMIL using Nd:YAG, Nd:GGG, Nd:glass, or Yb:S-FAP gain medium disks can be integrated into compact modules, which can be used to construct laser amplifiers and oscillators.…”
Section: Challenges To Developing Hap Sslmentioning
confidence: 99%
“…We have previously reported on a reflective disk laser with an alternative edge-pumped configuration [10][11][12][13][14] as shown in Figure 4 which overcomes many challenges associated with a face-pumped Ybbased disk laser. The original concept for a composite laser disk edge-pumped by flashlamps was also invented by Chernoch [15].…”
Section: Edge-pumped Disk Lasermentioning
confidence: 99%
“…Diode power is injected into the perimetral edge and channeled into the lasing (central) portion of the disk where it is gradually absorbed. Superposition of diode beamlets is balanced by absorption in the disk to provide uniform gain over the entire lasing volume [11,12]. The edge-pumped disk laser was test-verified in a DARPA-funded project, which showed that 96% pump uniformity is achievable under realistic conditions [13].…”
Section: Edge-pumped Composite Diskmentioning
confidence: 99%